2015
DOI: 10.1089/nat.2014.0510
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Aptamer Specific to Hsp70-ATP Conformation Inhibits its ATPase Activity Independent of Hsp40

Abstract: The highly conserved and ubiquitous molecular chaperone heat shock protein 70 (Hsp70) plays a critical role in protein homeostasis (proteostasis). Controlled by its ATPase activity, Hsp70 cycles between two conformations, Hsp70-ATP and Hsp70-ADP, to bind and release its substrate. Chemical tools with distinct modes of action, especially those capable of modulating the ATPase activity of Hsp70, are being actively sought after in the mechanistic dissection of this system. Here, we report a conformation-specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 64 publications
1
14
0
Order By: Relevance
“…In addition, the aptamer binding may also sterically block substrate binding to Hsp70. Previously, we demonstrated that the aptamer inhibited Hsp70 ATPase activity in the presence of Hsp40, but did not affect the stimulatory effect of Hsp40 on this ATPase activity [26], therefore the reduction of folding efficiency observed here is unlikely due to a destabilization of interaction between Hsp70 and Hsp40 by the aptamer. The destabilization of Hsp70-subsrate interaction may further affect Hsp70 capability to assist in substrate folding.…”
Section: Resultssupporting
confidence: 41%
See 4 more Smart Citations
“…In addition, the aptamer binding may also sterically block substrate binding to Hsp70. Previously, we demonstrated that the aptamer inhibited Hsp70 ATPase activity in the presence of Hsp40, but did not affect the stimulatory effect of Hsp40 on this ATPase activity [26], therefore the reduction of folding efficiency observed here is unlikely due to a destabilization of interaction between Hsp70 and Hsp40 by the aptamer. The destabilization of Hsp70-subsrate interaction may further affect Hsp70 capability to assist in substrate folding.…”
Section: Resultssupporting
confidence: 41%
“…1A), which indicated that the aptamer destabilized Hsp70-substrate interaction. Since the aptamer inhibits Hsp70 ATPase activity [26], it may be destabilizing Hsp70-substrate interaction by impeding the transition to Hsp70-ADP state that has a higher affinity for substrates [14,15,31,32]. In addition, the aptamer binding may also sterically block substrate binding to Hsp70.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations